Safety and tolerability of a combined oral contraceptive containing estetrol/drospirenone in real-life clinical practice: An open-label, prospective, multicenter, epidemiological, observational program "Estetiko" - Natalia V. Aganezova; Rushania I. Gabidullina (Гинекология)
Aim. To evaluate the safety and acceptability of a combined oral contraceptive (COC) containing estetrol 15 mg and drospirenone 3 mg when taken for 6 cycles in real clinical practice.